Perbankan Syariah dan Relevansinya dengan Pengembangan Ekonomi Syariah di Indonesia - Khairul Fadilah; Rozi Andrini (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Islamic banking in Indonesia has experienced rapid development since its introduction in the 1990s, contributing to the creation of a more inclusive and Islamic financial system. This study aims to analyze the role of Islamic banking in the development of the Islamic economy in Indonesia, with a focus on asset growth, adoption of digital technology, and its contribution to the micro, small, and medium enterprise (MSME) sector. Data shows that Islamic banking has experienced an average asset growth of 15-20% per year, with total assets reaching more than IDR 700 trillion by the end of 2023. In addition, digital innovations such as application-based banking services have increased the accessibility and efficiency of financial services for the community. Although Islamic banking faces challenges, such as a lack of human resources and fierce competition with conventional banks, this sector has great potential to support sustainable economic development and achieve the sustainable development goals (SDGs). This study is expected to provide new insights and strategic recommendations for the further development of Islamic banking and the Islamic economy in Indonesia, as well as increase public literacy regarding banking.